Synthesis, recording and metrology of laser beams with phase singularities - Ivanovskyy, A.A.; Basistiy, I.V.; Soskin, M.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The main task of the work was obtaining the high efficient diffraction elements to generate high quality laser beams with phase singularities. The method of recording such diffractive structures on the organic photoresist and further replication to the transparent and reflective materials is described. Off-axis and on-axis holograms of optical vortices with different topological charges were computer generated and recorded. The exposure characteristics of the photoresist Shipley S1800 was investigated. The maximum achieved diffraction efficiency was 30 % (for the normal incidence case). The quality of the intensity and phase distribution was investigated. As criteria of the beam quality we accept the relative coincidence between experimental and theoretical data. We assume that ratio more than 0.8 indicates the good fitness. For this assumption over 90 % of the beam energy produced by our computer generated hologram (CGH) concur with theoretical distribution. Our diffraction elements recorded on photoresist are much better that ones recorded on silver emulsion. They were successfully used in the experimental investigations in our laboratory.